POLICIES AND BUSINESS STRATEGIES OF WOMEN ENTREPRENEURS: STUDY ON BEAUTY BUSINESS NADISSE SALON - Erna Maulina; Meci Nilam Sari (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2017)
ABSTRACTThis paper contains about the implementation of business policy and strategy on beauty business Women Entrepreneur. The object studied is the salon NADISSE Bandung by discussing how the business strategy policy MSD salon NADISSE to be analyzed through internal environmental factors in the form of visible assets, invisible assets, and the capabilities of UMKM organizations. While external factors include the analysis of old competition, new competitors, replacement products, bargaining power of suppliers, and bargaining power of buyers in NADISSE salon SME business, and NADISSE Salon's competitive strategy includes promotion, product differentiation, and price leadership.Keywords: Business policy and strategy, SMEs, women entrepreneurs KEBIJAKAN DAN STRATEGI BISNIS WANITA PENGUSAHA:STUDI PADA USAHA KECANTIKAN SALON NADISSE ABSTRAK Tulisan ini berisikan tentang penerapan tentang kebijakan dan strategi bisnis pada usaha kecantikan Women Entreprneur. Objek yang diteliti adalah salon NADISSE Bandung dengan membahas bagaimana kebijakan strategi bisnis UMKM salon NADISSE yang akan dianalisis melalui faktor lingkungan internal yang berupa aset terlihat, aset tidak terlihat, dan kapabilitas organisasi UMKM tersebut. Sedangkan faktor externalnya meliputi analisis pesaingan lama, pesaing baru, produk penganti, daya Tawar pemasok, dan daya tawar pembeli pada bisnis UMKM salon NADISSE, serta strategi bersaing Salon NADISSE meliputi promosi, diferensiasi produk, dan kepemimpinan harga. Kata kunci: Kebijakan dan strategi bisnis, UMKM, wanita pengusaha